Photometry and colour index of Comet 67P/Churyumov-Gerasimenko on 2015 December 12. Issue 4 (5th June 2019) - Sen, A K; Hadamcik, E; Botet, R; Lasue, J; Roy Choudhury, S; Gupta, R
ABSTRACT: Comet 67P/Churyumov–Gerasimenko (hereafter, 67P) was observed on 2015 December 12, from 2 m Himalayan Chandra Telescope in India in photometry to study its dust properties, using Bessell R and I filters. We study the photometric images to highlight coma structures and jets. The radial decrease in intensity in the different coma structures is compared to the azimuthally integrated intensities. The observations of the slopes show a quasi-steady-state coma to an optocentric distance of about20 000 km. The change in the slopes in the structures indicates changing properties of the dust particles and/or change in their local size distributions. Comparison of the radial decrease in the two wavelengths suggests a change in the local colour index. Based on the absolute photometry carried out in this work, we calculate the reddening of the comet dust that helps to characterize variations in the size and the materials of the particles. The colour index is calculated for different apertures and regions in the coma (0.40 ± 0.07 mag) for a 22 000 diameter aperture. A colour map is constructed showing the variation of the colour index through the coma. Changes appear at the transition between the coma and the tail with a low colour index (<0.3 mag) close to the optocentre and further away increasing up in the tail direction (about 0.45 mag at10 000 km). We interpret these changes in terms of dust properties and we compare our results to other remote observations of 67P including in situ Rosetta observations.